2019
DOI: 10.21714/1984-3925_2019v22n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of political connections on the disclosure of social and environmental information

Abstract: Objective: To analyze the influence of political connections on the disclosure of social and environmental information. Method: The survey sample is composed of 370 companies listed on B3. To determine the level of socio-environmental disclosure, the sustainability reports for 2016 were analyzed, based on the guidelines of the Integrated Report (IR). As for the political connections, the existence of political or government shareholding in companies was analyzed, as well as the donations made by the companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Corruption has played an important role in scientific, political and economic debates worldwide (Garcia & Theodosius, 2020). In the corporate context, several publications have analyzed the relationship between the company's reputation and the contents of social and environmental reports (e.g., Koprowski et al, 2019;Odriozola & Baráibar-Diez, 2017). Other types of reports can also be included when addressing, for example, the image of a "corrupt" company and its relationship with interest groups (e.g., Barros, Rodrigues, & Panhoca, 2019;Etxeberria & Odriozola, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Corruption has played an important role in scientific, political and economic debates worldwide (Garcia & Theodosius, 2020). In the corporate context, several publications have analyzed the relationship between the company's reputation and the contents of social and environmental reports (e.g., Koprowski et al, 2019;Odriozola & Baráibar-Diez, 2017). Other types of reports can also be included when addressing, for example, the image of a "corrupt" company and its relationship with interest groups (e.g., Barros, Rodrigues, & Panhoca, 2019;Etxeberria & Odriozola, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Sancovschi and Silva (2006) described how Petrobras managers voluntarily disclosed social information in its annual reports from 1993 to 2002 to address negative aspects of its activities that could threaten its legitimacy. Koprowski et al (2019) focused on the socio-environmental aspects of reports from 370 companies listed on B3; they found that the weak institutional environment in Brazil, with deficient rules and regulations, favors corporate interests and political connections between companies and the government.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations